2015
DOI: 10.1001/jamaoncol.2015.1752
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parkinson Disease and Risk of Cancer in Taiwan

Abstract: Our study concludes that PD is is associated with most cancers in Taiwan. Further studies are needed to clarify whether our findings can be applied to other East Asian populations. The differences between our study and most previous cohorts suggest the importance of ethnicity and environmental exposures in disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 54 publications
5
89
1
3
Order By: Relevance
“…A Danish cohort study of 14,088 PD patients [16] and a case-control study of 8,090 Danish PD cases [17] also reported a positive association with ORs of 1.25 and 1.26, respectively. A positive relationship between PD and subsequent NMSCs was also reported in later studies [7, 18, 19], with point estimates ranging between 1.29 and 1.81 [1]. …”
Section: Discussionsupporting
confidence: 69%
“…A Danish cohort study of 14,088 PD patients [16] and a case-control study of 8,090 Danish PD cases [17] also reported a positive association with ORs of 1.25 and 1.26, respectively. A positive relationship between PD and subsequent NMSCs was also reported in later studies [7, 18, 19], with point estimates ranging between 1.29 and 1.81 [1]. …”
Section: Discussionsupporting
confidence: 69%
“…Although the pathway is a kind of brain disease, it contained many genes related to cell cycle71. Recent cohort study revealed the relationship between parkinson’s disease and cancer72. Also in molecular-level studies, the PARK2 and LRRK2 genes well known in parkinson’s disease were revealed that those genes were related with cell cycle pathways7374.…”
Section: Resultsmentioning
confidence: 99%
“…After full article review for the remaining 33 studies, 7 duplicated studies which were performed in the same population and 11 studies which did not meet inclusion criteria were excluded (Supplementary material 1). Finally, 15 studies were included in our meta-analysis [57, 1122] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…In addition, we excluded two studies which were based on Asian population [7, 11] and performed further analyses in Western population. The pooled result showed that patients with PD were significantly associated with a decreased risk of lung cancer in Western population (RR: 0.48, 95% CI: 0.39–0.60, P < 0.001, I 2 = 85%, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation